Comparison of protective effects of electroacupuncture and moxibustion at Zusanli (ST 36) on perinatal nicotine exposure-induced lung phenotype in rat offspring - Yunpeng Ge; Yitian Liu; Guozhen Zhao; Reiko Sakurai; Yana Xie; Tianyu Shi; Yang Fang; Jiajia Wang; Virender K. Rehan; Bo Ji (Journal of Traditional Chinese Medical Sciences, 2023)
Objective: To compare the effects of electroacupuncture (EA) and moxibustion at Zusanli (ST 36) on the lung phenotype of rat offspring exposed to nicotine during the perinatal period. Methods: Pregnant Sprague-Dawley rats were randomly divided into 4 groups: the control group (saline only), the model group (nicotine only), the EA group (nicotine + EA at ST 36 acupoints bilaterally), and the moxibustion group (nicotine + moxibustion at ST 36 acupoints bilaterally). n = 6 rats per group. On postnatal day 21, the body weight, lung weight, and pulmonary function were determined and lung morphometry was performed. Peroxisome proliferator-activated receptor gamma and β-catenin levels in the lung tissue of offspring were also determined. Results: Perinatal nicotine exposure (PNE) results in decreased body and lung weights of offspring rats, abnormal lung tissue morphology, and significantly altered pulmonary function, showing an increase in total airway resistance and a decrease in tidal volume, minute ventilation, total airway compliance, and peak expiratory flow. Bilateral EA at ST 36 acupoints could block all of these perinatal nicotine-induced effects. Although moxibustion also had protective effects in nicotine-induced offspring lungs, some of these effects did not reach statistical significance, e.g., protection against the upregulation of β-catenin, the downregulation of PPARγ signaling, and the increase in peak expiratory flow. Conclusion: Maternal EA at ST 36 blocked the PNE-induced changes in key developmental signaling pathways, prevented the PNE-induced changes in lung morphology, and protected pulmonary function. Moxibustion at ST 36 showed similar but weaker protective effects against the PNE-induced changes in the exposed offspring. It is important to note that the mechanism underlying the protective effects of moxibustion at ST 36 may be different from those of EA at ST 36, and further research is needed to understand these differences.